Konsumsi Ikan dan Potensi Anisakiasis: Aspek Komunikasi Kesehatan Masyarakat Suatu Program Pemerintah - Ekarini Daroedono (Fakultas Kedokteran Universitas Riau, 2019)
Communication in the health sector plays an important role in the context of educating people and the society. The emphasis is rely primarily on promoting health so that behavior changes occur. One of the example is a government program “GEMARIKAN” which was designated to increase fish consumption in the community. Unfortunately, the triumph upon this programme is overshadowed by the potential transmission of zoonotic infections of the nematode worm named Anisakis spp. This worm can caused a potentially fatal and deadly disease called anisakiasis. This risk can be reduced by re-conducting numerous education in the community regarding these parasites, their life cycles, its host behaviors and lifestyles that can facilitate transmission such as eating fish in raw conditions and the need of good handling practices of fish to avoid transmission to occur.